2019
DOI: 10.18805/lr-398
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiological and yield attributes of groundnut varieties under different salinity stress conditions

Abstract: The study sought to evaluate the response of three groundnut genotypes (Binachinabadam-3, Dacca-1 and Zhingabadam) to various salt concentrations (D0 – Control, D1 – 2.5 dS/m, D2 – 5.0 dS/m, D3 – 7.5 dS/m, D4 – 10.0 dS/m, D5 – 12.5 dS/m) through observation of morphological and physiological characters. Based on relative performance of yield contributing characters and nutrient contents of leaves and stem, Binachinabadam-3 emerged to be a tolerant variety and based on root shoot characters, Dacca-1 appeared as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Among these technologies, the use of salt-tolerant crops (Bhardwaj & Kapoor, 2021) and water management practices, such as pulse drip irrigation (Cruz et al, 2018), can be mentioned. Peanut is a crop moderately sensitive to salinity (Yasmine et al, 2019), as already verified in other studies (Alves et al, 2016;Cruz et al, 2018;Yasmine et al, 2019). Therefore, salt stress causes damage to the growth and morphogenesis of peanut, reducing the germination of the seeds and the accumulation of dry matter, influencing the establishment of the morphology of the seedlings and inducing damage to the photosynthetic apparatus (Tian et al, 2019).…”
Section: Introductionmentioning
confidence: 71%
“…Among these technologies, the use of salt-tolerant crops (Bhardwaj & Kapoor, 2021) and water management practices, such as pulse drip irrigation (Cruz et al, 2018), can be mentioned. Peanut is a crop moderately sensitive to salinity (Yasmine et al, 2019), as already verified in other studies (Alves et al, 2016;Cruz et al, 2018;Yasmine et al, 2019). Therefore, salt stress causes damage to the growth and morphogenesis of peanut, reducing the germination of the seeds and the accumulation of dry matter, influencing the establishment of the morphology of the seedlings and inducing damage to the photosynthetic apparatus (Tian et al, 2019).…”
Section: Introductionmentioning
confidence: 71%
“…Previous reports suggested that there is huge genetic diversity in the salt tolerance among peanut germplasms ( Pal and Pal, 2022 ). The agronomic traits such as survival under salt stress, plant height, relative growth rate reflected the salt tolerance of peanut ( Yasmine et al., 2019 ). The salt tolerance coefficient that was calculated as biomass accumulation ratio under salt stress to unstressed control in each genotype was considered as selection criteria for salt tolerance in peanut ( Pal and Pal, 2022 ).…”
Section: Discussionmentioning
confidence: 99%